Educação especial e tecnologias digitais: o cineclube como possibilidade formativa na perspectiva freireana - Kaczmarek, Marli (2022)
Digital technologies are seen as a category of new technologies that can contribute to education. However, the interdependence of objective and subjective conditions influences social contexts, particularly in formal education. Hence, the question arises: to what extent can digital technologies, specifically cineclub practices, contribute to a dialogic and liberating process in continuous education on Human Rights in special education at the basic level? With that in mind, the general goal is to design a flexible and complementary proposal for cineclub in the Freirean perspective of Human Rights for continuous education among teachers in special education at the basic level. Whereas the specific goals are: a) to analyze the possibilities of using digital technologies in dialogic and liberating educational processes; b) to identify mechanisms that intensify social exclusion and inequality in education; c) to establish possible links between hunger, meritocracy, and school grades; d) to reflect on the fundamental democratization process of education; e) to reflect on the process of continuous education on Human Rights; f) to structure, through examples, possible educational opportunities for cineclub practices. The analytical perspective is phenomenological, mainly based on the contributions of the works of Paulo Freire (1983, 1986, 1996, 2001, 2013) and Dartigues (1992). The research approach is qualitative-quantitative and exploratory, adopting bibliographic and documentary methods. The results indicate that cineclub practices can contribute to pedagogical reflections and actions in special education at the basic level, beyond formal education, when carefully planned according to the dialogic and liberating perspectives of Paulo Freire on Human Rights. Paradoxically, although foreseen in the National Education Guidelines and Framework Law (LDBN), this practice is not yet consolidated, requiring awareness about the need for and importance of investing in public policies for its implementation as an integral part of the fundamental democratization process of education.